Neuropharmacological Interventions of Plant Origin for Parkinson's Disease: A Comprehensive Appraisal - Muzaffer, Umar; Gull, Bisma; Ahmed, Zabeer; Ahmad, Muzamil (Current Neuropharmacology, 2025)
Parkinson's disease (PD) presents a complex challenge in neurodegenerative disorders, necessitating innovative therapeutic approaches. This review article elucidates the therapeutic potential of traditional herbal formulations alongside computational methods in PD research. Through comprehensive examination, we explore their mechanisms of action, synergistic effects, and implications for PD management. Furthermore, we discuss the significance of computational techniques such as molecular docking, molecular dynamics simulations, pharmacophore modeling, and network pharmacology. Our analysis underscores the integration of traditional wisdom with modern scientific inquiry, paving the way for nuanced interventions in PD.
Keywords: natural compounds